Persistent organic chemicals in Malaysian waters: a review. - Somchit, N.; Somchit, M.N.; Saat, Azizan Hadi; Zakaria, Mohamad Pauzi (Academic Journals, New York, 2009)
A critical review of the levels of persistence organic chemicals in Malaysian waters from 1980 to 2002. This review concentrated on the detection several toxic substances by groups of scientists in the marine environment, evaluated their quantities and provides estimates of their potential danger for the health of both marine life and humans. The compounds include polycyclic aromatic hydrocarbons, tributyl-tin and pesticides. In summary, the levels of some persistent organic chemicals is lower compared with other Southeast Asia countries and the levels in this region still at the medium level compared with more urbanized and industrialized regions in the West. Nevertheless, continuous monitoring and investigations on the level of the persistent organic chemicals are needed in Malaysia. Transboundary pollution potential should be taken as an important consideration in any development project especially in Southeast Asia.